Training of Trainers 4.0 Industri Kecil Menengah Furnitur Untuk Mendorong Transformasi Digital Dengan Teknologi Internet of Things - Kristianto, Fesa Putra; Broto, Taukhid Wisnu; Puspitaningsih, Fitri Indah (Journal of Industrial Community Empowerment, 2024)
The furniture industry in Central Java still faces various challenges, especially in adopting advanced technologies such as the Internet of Things and Industry 4.0. Many furniture SMEs still rely on manual or semi-manual production methods, which result in suboptimal product quality and production efficiency, making it difficult to compete in the global market. To address these challenges, the Community Service Program carried out by the Furniture Industry Business Management Study Program at Polytechnic of Furniture Industry and Wood Processing actively played a role through the Training of Trainers activity. This program aims to provide intensive training on the implementation of IoT and Industry 4.0 technologies to furniture SMEs in Central Java, focusing on developing practical skills and fostering digital transformation. Training of Trainers training involved Furniture Industry Business Management lecturers who possess specialized expertise in Industry 4.0 technologies. The training covered both theoretical and practical aspects, allowing participants to not only understand the concepts but also implement them in their work environments. Evaluation results showed a significant increase in the participants' understanding and skills in applying Industry 4.0 and Internet of Things technologies. A tangible example of the success of this training is PT. AST Indonesia, which successfully implemented Industry 4.0 and Internet of Things technologies in its production processes after participating in the Training of Trainers program. This success is concrete evidence that the training provided by Furniture Industry Business Management can contribute significantly to enhancing the competitiveness of furniture SMEs in the digital era, in line with the vision of "Making Indonesia 4.0.